Propagation of Surfactant‐Dispersed Multiwalled Carbon Nanotubes in Porous Media. Issue 5 (5th July 2019) - Chen, Changlong; Wang, Shengbo; Wang, Shuoshi; Yuan, Na; Li, Keren; Shiau, Bor‐Jier; Harwell, Jeffrey H.
Abstract: Understanding the transport of carbon nanotubes in porous media is essential to their applications in subsurface reservoirs, e.g., delivering catalysts or chemicals to targeted formations. In this study, a series of laboratory experiments are conducted to explore the transport of surfactant‐dispersed multiwalled nanotubes (MWNT) in different porous media in flow‐through columns at elevated electrolyte levels. Noncovalent bonding of ethoxylated alcohols adsorbed on the MWNT surface provides them with outstanding dispersion stability and excellent transport properties in a crushed‐limestone sand pack. Superior transport performance in silica sand is obtained with binary nonionic–anionic surfactant formulations, which provide both steric repulsion and electrostatic repulsion between nanoparticle–nanoparticle and nanoparticle–sand surface. The mobility of MWNT suspensions are further investigated in the exposure to multiphase flow, e.g., with residual oil present, or coinjected with air into the sand pack. Coinjecting surfactant‐dispersed MWNT suspensions with air (i.e., MWNT‐stabilized foams) has hardly any impact on their propagation; retention in the sand pack remains quite low. With the presence of oil in the sand pack, the transport of MWNT suspensions is highly dependent on the type of surfactants used as the dispersant. For surfactants that achieved modest interfacial tension (IFT) reduction, the injected MWNT suspension bypasses the oil phase, and little impact on retention is observed. When the dispersant surfactant is also adjusted for an ultralow IFT condition, greater MWNT retention in the porous medium is observed because surfactants detach from the MWNT surface and aggressively partition to the oil/water interface, allowing the MWNT to flocculate and become deposited in the porous medium.